The Future of Machine Learning: Supervised, Unsupervised and Reinforcement Learning - Chakraborty, Anirban (International Journal on Orange Technologies, 2023)
The Machine Learning is a data analysis technique that automates the development of analytic models. It is an important field of study based on the premise that machine data can be studied and that trends and judgments can be made with little human input. On the basis of fresh discoveries, machine learning algorithms may be constructed from provided data.